Parents' and Service Providers' Experiences of Accessing Health Services from an Intellectual Disability Health Team - Denise Campbell; Jacqueline Milne; Pankaj Garg; Gail Tomsic; Natalie Ong; Natalie Silove (SAGE Publishing, 2021)
A pediatric assessment service for children with Intellectual Disability (ID) was established in a culturally diverse region of Sydney, Australia, to meet the health needs of children and young people with ID. This paper reports on parents' and providers' experiences using qualitative and quantitative analysis of surveys. The survey responses from the parents' enumerated their key concerns and the practical help they received from the service. Responses from service providers reported a high level of satisfaction with the services and valued the quality of assessment reports. The service facilitated inter-agency collaboration and enhanced the access to quality health care.